Analisis Faktor – Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi pada Lembaga Perkreditan Desa (LPD) di Kecamatan Manggis - Apriada, Kadek; Hardianti, Putu Novia Hapsari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research in LPD aims to find out about expertise, the existence of a board of directors, the use of information technology, work experience, and nyama braya on the performance of the accounting information system at the Village Credit Institution in Manggis District. The research sample consisted of 96 LPD employees selected through purposive sampling. This study shows that the variables of information technology utilization, work experience, and nyama braya have a positive effect on the performance of the accounting information system. The variables of expertise and the existence of a board of directors do not have a significant effect on the performance of the accounting information system. The implication is that there needs to be a focus on increasing the use of information technology, developing experience, nyama braya to improve the effectiveness and efficiency of LPD operations. In the context of LPD management, understanding these findings can be a reference for improving human resource management and information technology strategies.